Inhibitory Immune Checkpoint Receptors and Ligands as Prognostic Biomarkers in COVID-19 Patients - Al-Mterin, Mohammad A.; Alsalman, Alhasan; Elkord, Eyad (Frontiers in Immunology, 2022)
Coronavirus disease 2019 (COVID-19) is caused by SARS-CoV-2. During T-cell activation, the immune system uses different checkpoint pathways to maintain co-inhibitory and co-stimulatory signals. In COVID-19, expression of immune checkpoints (ICs) is one of the most important manifestations, in addition to lymphopenia and inflammatory cytokines, contributing to worse clinical outcomes. There is a controversy whether upregulation of ICs in COVID-19 patients might lead to T-cell exhaustion or activation. This review summarizes the available studies investigated IC receptors and ligands in COVID-19 patients, as well as their effect on T-cell function. Several IC receptors and ligands, including CTLA-4, BTLA, TIM-3, VISTA, LAG-3, TIGIT, PD-1, CD160, 2B4, NKG2A, Galectin-9, Galectin-3, PD-L1, PD-L2, LSEectin, and CD112, were upregulated in COVID-19 patients. Based on the available studies, there is a possible relationship between disease severity and increased expression of IC receptors and ligands. Overall, upregulation of some ICs could be used as prognostic biomarkers for disease severity.